2019
DOI: 10.3390/genes10050334
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Genetic Dissection of Sucrose Inputs to the Arabidopsis thaliana Circadian System

Abstract: Circadian rhythms allow an organism to synchronize internal physiological responses to the external environment. Perception of external signals such as light and temperature are critical in the entrainment of the oscillator. However, sugar can also act as an entraining signal. In this work, we have confirmed that sucrose accelerates the circadian period, but this observed effect is dependent on the reporter gene used. This observed response was dependent on sucrose being available during free-running condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…For the experiments presented in Figures 3A,B, the plants harboring GI:LUC construct were entrained for 5 days under 12-h light/12h dark photoperiod at a constant temperature of 22 • C before entering continuous darkness at dusk. This was similar to the carbon and sucrose examinations by Perea-García et al (2015); Perea-Garcia et al (2016), and Philippou et al (2019). Briefly, every 3 h, a subset of plants was retrieved from the basal growth medium (MS) and subjected to non-parametric entrainment with 3-h light pulses (WL) on the growth medium that contained SA at 1 mM or DMSO.…”
Section: Light/chemical Pulse Experimentsmentioning
confidence: 84%
See 1 more Smart Citation
“…For the experiments presented in Figures 3A,B, the plants harboring GI:LUC construct were entrained for 5 days under 12-h light/12h dark photoperiod at a constant temperature of 22 • C before entering continuous darkness at dusk. This was similar to the carbon and sucrose examinations by Perea-García et al (2015); Perea-Garcia et al (2016), and Philippou et al (2019). Briefly, every 3 h, a subset of plants was retrieved from the basal growth medium (MS) and subjected to non-parametric entrainment with 3-h light pulses (WL) on the growth medium that contained SA at 1 mM or DMSO.…”
Section: Light/chemical Pulse Experimentsmentioning
confidence: 84%
“…It is noteworthy that, under red light (Figure 5C), the toc1-21 mutant exhibited a long period phenotype, whereas under BL we recorded a short period phenotype of the toc1-21 mutant ( Figure 5D and Supplementary Table S23), which was not affected by SA application. Previously, we have shown that the lhy-21, cca1-11, and gi-11 mutants also show sucrose-dependent phenotypes (Philippou et al, 2019).…”
Section: Supplementary Tables S6 S7mentioning
confidence: 91%
“…Exogenous sucrose has previously been used to saturate plants' circadian responses to photoassimilates (Frank et al, ; Haydon et al, ; Haydon et al, ; Philippou et al, ). Interestingly, exogenous sucrose was sufficient to mask the cry1 circadian defect under constant green light but not constant blue light (Figures c and S4b).…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of light signalling into the circadian system is complicated by the clock's response to metabolites derived from photosynthesis (Frank et al, ; Haydon et al, ; Haydon et al, ; Philippou et al, ). In order to assess the contribution of photosynthesis towards circadian rhythmicity under constant green light, we assessed circadian rhythms in the presence of CO 2 ‐depleted air (Figures d and ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation